Sphaerodoridae (Annelida) from Lizard Island, Great Barrier Reef, Australia, including the description of two new species and reproductive notes - Capa, María; Rouse, Greg W. (Zootaxa, 2015)
Sphaerodorids are scarce at Lizard Island archipelago and other localities in the Great Barrier Reef, Australia. Intensive collections at a variety of habitats within the Lizard Island archipelago over the last four decades have resulted in a total of just 11 specimens. Nevertheless, they represent two new species and a new record for Lizard Island. Sphaerodoropsis aurantica n. sp. is characterised by nine longitudinal rows of sessile and spherical dorsal macrotubercles, arranged in a single transverse row per segment; parapodia with around 10 spherical papillae; and compound chaetae with thin shafts and long blades. Sphaerodoropsis plurituberculata n. sp. is characterised by more than 12 more or less clearly arranged longitudinal rows of sessile spherical dorsal tubercles (variable in size), in four transverse rows per segment; parapodia lacking papillae; and semi-compound chaetae with distally enlarged shaft and short blades. Ephesiella australiensis is reported for the first time in Lizard Island. Laboratory observations of live specimens of Sphaerodoropsis plurituberculata n. sp., revealed the use of spermatophores by males. These were found attached externally to the body surface of both sexes, indicating pseudo-copulation.